Does spatial sorting occur in the invasive Asian toad in Madagascar? Insights into the invasion unveiled by morphological analyses. (26th August 2021) - Licata, Fulvio; Andreone, Franco; Crottini, Angelica; Harison, Rodino Fetraharijaona; Ficetola, Gentile Francesco
Abstract: Dispersal‐relevant traits may be subjected to spatial sorting in rapidly expanding populations, driving the evolution of dispersive phenotypes. This process has been largely documented in invasive species, and ascertaining its presence can have important implications for their management. The Asian common toad was accidentally introduced to Madagascar around 2010 and is a highly problematic invasive species. Exploring the morphology of this species offers the twofold opportunity to test the hypothesis of early onset of spatial sorting and to gather information on the dynamics of this unstudied biological invasion. For these purposes, we analyze morphological data of adult toads collected across the invasive range in Madagascar, and we test the effect of the distance from the introduction point on the relative size of head, radioulna and tibiofibula, and on body size and body condition of toads, respectively. We did not detect evidence of spatial sorting in the morphological traits analyzed. Instead, morphological variation was largely dependent on sex and body size of individuals. Sexual dimorphism was limited in relation to other populations in the native range, and body size did not vary across the invasive gradient, which could indicate that both adults and juveniles are currently contributing to the dispersal in this invasive species. We provide important baseline data for the long‐term assessment of morphological variation in the invasive population, and we advocate for further investigations of spatial sorting in life history and behavioral traits. Abstract : Spatial sorting of dispersal‐relevant traits may occur in rapidly expanding populations, driving the evolution of dispersive phenotypes. In invasive species, this process can have important implications for their management. We investigate the morphology of the invasive Asian common toad in Madagascar to detect spatial sorting and to gather information on the invasion dynamics of this highly problematic invasive species. Results exclude the presence of spatial sorting in the traits analyzed, but bring important new insights into the invasion dynamics. Riassunto: Nelle popolazioni in rapida espansione i tratti rilevanti per la dispersione possono essere soggetti a spatial sorting, portando all'evoluzione di fenotipi dispersivi. Questo processo è stato ampiamente documentato nelle specie invasive, ed accertarne la presenza può avere importanti implicazioni nella loro gestione. Il rospo asiatico comune è stato accidentalmente introdotto in Madagascar intorno al 2010 ed è una specie invasive altamente problematica. Studiare la morfologia di questa specie offre la duplice opportunità di testare l'ipotesi di insorgenza precoce di spatial sorting e raccogliere informazioni sulle dinamiche di questa invasione poco studiata. A tal fine, analizziamo i dati morfologici di rospi adulti raccolti nella regione del Madagascar interessata dall'invasione, e testiamo l'effetto della distanza dal punto d'introduzione sulla taglia relativa di testa, radioulna e tibiofibula, e sulle dimensioni e la condizione corporea dei rospi. I risultati non mostrano evidenze di spatial sorting nei tratti morfologici analizzati, ma indicano che la variazione morfologica dipende in gran parte dal sesso e la dimensione degli individui. Il dimorfismo sessuale è ridotto rispetto alle popolazioni nell'areale nativo, e la taglia dei rospi non variava lungo il gradiente dell'invasione, il che potrebbe indicare che sia adulti che giovani contribuiscono alla dispersione in questa specie invasiva. In quest'articolo, forniamo dati importanti per una valutazione a lungo termine della variazione morfologica di questa popolazione invasiva e indichiamo l'importanza di ulteriori indagini sullo spatial sorting nei tratti biologici e comportamentali di questa specie.